A new stakeholder management framework for EPCM Projects: Analysis of approaches used by Australian and Chinese Project Managers in Africa - Wembe, Paulin Tchumtcha (Curtin University, 2015)
This research develops a new stakeholder management framework based on best practices of Australian and Chinese approaches in Engineering, Procurement and Construction Management projects in Africa. Managing stakeholders in EPCM projects in Africa are characterised by two distinct management approaches that can be broadly classified as Australian and Chinese models. The research combines the best practices of both to develop a new framework that helps project managers managing stakeholders in EPCM projects in Africa.